PROPOSAL DESAIN KURIKULUM PENDIDIKAN AGAMA KRISTEN (PAK) DEWASA BERPUSAT PADA TEKNOLOGI (TECHNOLOGICAL-CENTERED DESIGN) DI GEREJA - Anen Mangapul Situmorang; Alexander Naulus Rupidara (Sesawi, 2023)
Adults are considered as an age category that is able to use digital technology in various ways, such as for the benefit of working, undergoing education, and communicating. Therefore, in the context of adult education, the use of digital technology is very effective in the learning process. This is really needed in this era considering that adults are of productive age. They have very busy schedules so they don't have much time to receive education, especially Christian religious education (PAK) which is organized formally, informally and non-formally. Based on the adult situation, the use of digital technology in adult learning is the right choice. For this purpose, adult educators must prepare a technology-centered design curriculum. However, the problem is that there are still many adult PAK educators who do not understand what is meant by this curriculum design and how to develop it. Therefore, the purpose of this research is to describe the technological-centered design of the adult Christian religious education curriculum.